Happy this year! : the secret to getting happy once and for all - Bowen, Will (Grand Harbor Press, 2013)
International bestselling author Will Bowen teaches listeners how to align their thoughts, words, and actions so that they create the habits, character, and destiny of happiness. Through practical advice, step-by-step instructions, and inspiring stories, Will helps readers remove their mental and lifestyle blocks so that happiness flows freely.